Folk music : a very short introduction - Slobin, Mark (Very short introductions, 2011)
When we think of folk music, most of us picture Pete Seeger singing "This Land is My Land" or Joan Baez singing "Barbara Allen." But this stimulating Very Short Introduction throws open the doors on a remarkably diverse musical genre, in a wide-ranging portrait that goes far beyond America's shores to discuss folk music of every possible kind and in every corner of the globe. Written by award-winning musicologist Mark Slobin, this is the first compact introduction to folk music that offers a truly global perspective. Slobin offers an extraordinarily generous portrait of fol